2013
DOI: 10.1055/s-0032-1325992
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of 22-gauge and 25-gauge needles in endoscopic ultrasound-guided fine needle aspiration of solid pancreatic lesions: a meta-analysis

Abstract: This meta-analysis suggests 25 G needle systems are more sensitive than 22 G needles for diagnosing pancreatic malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
159
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(168 citation statements)
references
References 19 publications
3
159
4
2
Order By: Relevance
“…A 25-gauge needle is therefore recommended to puncture the head of the pancreas 4 . Several studies have compared the performance characteristics of a 22-gauge needle with those of a 25-gauge FNA needle for sampling pancreatic masses, but most have failed to demonstrate superiority of either needle [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . A recent systematic review and meta-analysis of EUS-FNA for solid pancreatic masses, including a large cohort of patients, revealed that a 25-gauge needle was more sensitive than a 22-gauge needle 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A 25-gauge needle is therefore recommended to puncture the head of the pancreas 4 . Several studies have compared the performance characteristics of a 22-gauge needle with those of a 25-gauge FNA needle for sampling pancreatic masses, but most have failed to demonstrate superiority of either needle [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . A recent systematic review and meta-analysis of EUS-FNA for solid pancreatic masses, including a large cohort of patients, revealed that a 25-gauge needle was more sensitive than a 22-gauge needle 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The FNA technique and use of needle gauge was not standardized in our study, but rather, left at the discretion of the endosonographer in this multicenter RCT in order to best simulate true clinical practice in addition to the fact that there is lack of level 1 evidence that these variables significantly affect the diagnostic yield. Meta-analysis data has demonstrated increased diagnostic yield of 25-G needles for pancreatic mass lesions, howeve,r in our RCT there was no significant difference between needle gauge in the FNA and FNB groups in our study, thus eliminating any potential bias or benefit in either group [30,50]. Our study was performed at high-volume tertiary centers, therefore, there was a bias toward malignant lesions.…”
Section: Discussionmentioning
confidence: 50%
“…A meta-analysis of 22-gauge needles versus 25-gauge needles for FNA of solid pancreatic masses showed that 25-gauge needles were more sensitivity than 22-gauge needles for the diagnosis of malignancy (93% versus 85%). 17 The 25-gauge needles were again superior over 22-gauge but also over 19-gauge Trucut core biopsy needles as well. 18 Additional core biopsy needles have been developed as well.…”
Section: Q2mentioning
confidence: 94%